Microstructures of nickel-doped methylated silica membrane materials calcined in air: influence of Ni content. (3rd July 2020) - Yang, Jing; Xing, Xiaoting; Zhao, Yamei; Mu, Ruihua; Guo, Yani; Hou, Haiyun
Abstract: Nickel-doped methylated silica membrane materials (Ni/CH3 -SiO2 ) were prepared with tetraethylorthosilicate (TEOS) and methyltriethoxysilane (MTES) as silicon precursors, and Ni(NO3 )2 ·6H2 O as Ni source by sol-gel method. The effects of Ni content on the microstructures of Ni/CH3 -SiO2 membrane materials were investigated by means of X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and N2 adsorption-desorption measurements. The results indicate that the Ni element is present in the form of Ni(NO3 )2 ·6H2 O in the gel material. After firing at 350 °C in air, the Ni element mainly exists in the form of Ni-O-Si skeleton and nano-crystalline NiO. As the Ni content increased, the dispersity of NiO particles reduced and the grain size increased gradually. The methyl group is present in the Si-CH3 form in the SiO2 network. After the loading of Ni, the total pore volume decreased while the average pore size increased. The prepared 0.1Ni/CH3 -SiO2 membrane material exhibited excellent microporous structure and narrow pore size distribution with the average pore size of 1.94 nm. Its microporosity reached 79.9%, which increased by 17.9% compared with the CH3 -SiO2 material without Ni-loading.